Efficacy of THN102 (a combination of modafinil and flecainide) on vigilance and cognition during 40‐hour total sleep deprivation in healthy subjects: Glial connexins as a therapeutic target. Issue 11 (15th September 2019) - Sauvet, Fabien; Erblang, Mégane; Gomez‐Merino, Danielle; Rabat, Arnaud; Guillard, Mathias; Dubourdieu, Dominique; Lefloch, Hervé; Drogou, Catherine; Van Beers, Pascal; Bougard, Clément; Bourrrilhon, Cyprien; Arnal, Pierrick; et al.
Abstract : Aims: THN102 is a novel combination of modafinil and low‐dose flecainide, targeting glial connexin activity to modulate modafinil effects. We investigated THN102 efficacy compared to modafinil and to placebo on vigilance and cognitive function during 40‐hour total sleep deprivation (TSD). Methods: Twenty healthy men participated in a double‐blind, randomized, incomplete‐block 3‐period cross‐over trial with 5 treatments ( n =  12 per group): placebo (PBO), modafinil 100 mg (MOD100), THN102 100/1, 100/3, 100/9 (modafinil 100 mg and flecainide 1, 3 or 9 mg). Each period included a baseline day and a TSD day with treatments administered 3 times (01:00, 09:00 and 19:00). Reaction time in psychomotor vigilance test, subjective somnolence and vital signs were assessed before and during treatment. Working memory (2‐Back) and executive processes (Go/noGo for vigilance and inhibition, Wisconsin card sorting task for mental flexibility, and Tower of London test for planning) were evaluated at 16:30. Results: At 5 hours postdose−1 (after 23 hours TSD, primary endpoint), THN102 100/1 resulted in statistically higher psychomotor vigilance test speed vs MOD100 (3.97 ± 0.09 vs 3.74 ± 0.14, P < .05). No increase in effect was observed with higher flecainide doses in combinations. Most THN102 doses vs MOD100 also improved the number of correct responses in 2‐Back and Go errors in Go/noGo ( P < .05 for all doses), and perseverative responses in Wisconsin card sorting task (for 100/1 and 100/9). No impact on cardiac conduction was noted with THN102, and safety was similar to MOD100. Conclusions: THN102 seems more efficient than modafinil on vigilance, working memory and executive functions, opening new perspectives in management of hypersomnolence disorders.